Team-Based Learning for Immunology Courses in Allied Health Programs - James, Stephanie; Cogan, Peter; McCollum, Marianne (Frontiers in Immunology, 2019)
Immunology is now a major component of studies in human biology, with many diseases having immune system involvement. Because so many areas of study include aspects of immunological knowledge, how to teach and incorporate immunology must be evaluated and assessed at all levels of education including K-12, undergraduate, graduate, medical, and professional programs. Traditional teaching methods such as lecture have significant shortcomings which make them less appealing to students today who are more digitally inclined and demand more active and engaging learning environments. Herein, we describe and propose the use of the active learning model of Team-Based Learning (TBL) to incorporate immunology into medical and professional programs. TBL is defined as an evidence based collaborative learning strategy taught in a three-step cycle: pre-class preparation, in-class readiness assurance testing (RAT), and application-focused exercises. In TBL, students are assigned to 6–7 member teams. Students complete the in-class RAT individually followed by taking the RAT as a team (T-RAT). Following the RAT and T-RAT, the instructor can then provide immediate feedback on concepts that proved especially difficult. The remainder of class time is then spent with teams working case studies and applications relative to the instructional topic or disease. Teams decide the best outcome or answer for a given application and report their answers simultaneously in class, followed by a discussion facilitated by the instructor. Research indicates that students involved in active learning classes, such as those using TBL have significantly increased levels of student engagement and high performance on examinations. This review will highlight how to implement TBL into a professional program (medical, dental, nursing, or pharmacy), how to assess student performance and provide real world examples of case studies and applications.